An exploratory qualitative study AR self-care flashcards - Adnan, Norhidayah; Mustafa, Siti Ezaleila (Faculty of Art and Design, 2025)
Technology can help educators assist the learning and teaching process in the classroom. This focus needs more encouragement for preschool children who are prone to autism in the context of self-care. These autistic children need to be focused on self-care to prepare them to go to school, as a daily routine, and the basic needs of their social skills. This technology can give them a more enjoyable learning atmosphere with interaction and excitement to use applications and tools. These two contexts have been given early exposure from home. However, the lack of development of teaching materials for these children is significant because of the lack of time and expertise in developing this learning and teaching aid application. The development of teaching aids that are on the market today refers more to blind and mute children, such as studies in the learning system for them that have been widespread. This study aims to examine the appropriate self-care content for autistic children and develop a self-care flashcard application designed with the use of augmented reality technology; the purpose of the development of a self-care flashcard application from educators by personal interview approach states that this study can help make it easier for educators to control the learning environment in the involvement of autistic children to understand self-care in the classroom. Findings identify that personal hygiene and self-feeding skills such as brushing teeth, eating, and bathing are essential for fostering independence in autistic preschool children; these skills align with structures and repetitive teaching methods instead of using traditional flashcards to AR flashcards application as their unique learning styles.